Community-Based Tourism Dimension Approach: The Existence of Digital Marketing in the Coastal Communities of the Riau Islands Province - David Humala Sitorus; Lismayasari (Institute of Computer Science (IOCS), 2020)
This study aims to respond to an alternative review of tourism-based communities as an effort to contribute to the state and small communities with breakthroughs in economic acceleration and poverty alleviation programs for local communities in tourist villages throughout the Riau Islands province. In contrast and normatively, the division of tourism concepts cannot be separated from branding and regional characteristics of cultural and ethnic concepts. Technological intervention indicates that there is a schematic and constructive relationship pattern related to the differentiation of the need for tourism consumption which is the fruit of the concept of community-based tourism. Researcher contextually, namely, three supporting dimensions that provide a strong foundation for the program to improve the economic construct of local communities in the Riau Islands province, namely Branding, tourism-based communities, the existence of the surrounding community, community creativity, and stakeholders in it. This study uses a quantitative survey method with samples taken from 160 tourism village residents who have used digital technology related to product marketing for the branding process of local areas for visitors to tourist attractions in the province of Riau Islands. This research is survey research where the data analysis process uses Structure Equation Model analysis with a continuous analysis base pattern.